연령관련황반변성 환자에서 항혈관내피성장인자의 치료 방법과 재정 영향 분석 - 양장미(Jangmi Yang), 신상진(Sang Jin Shin), 서재경(Jae Kyung Suh), 조송희(Songhee Cho), 최하진(Hajin Tchoe), 강민주(Min Joo Kang), 지동현(Donghyun Jee) (Daihan angwa haghoi jabji, 2018)
목적: 연령관련황반변성 환자에 대해 항혈관내피성장인자의 가능한 치료 방법에 따라 건강보험 재정에 미치는 영향을 분석하였다. 대상과 방법: 여러 치료 방법에 따른 건강보험 재정의 변화를 향후 5년(2018‐2022년) 동안 추정하였다. 새로운 급여기준 이외 바이오시밀러 등장, 허가초과 비급여약제 사용 등을 고려한 시나리오에 대해서도 재정 영향을 분석하였다. 국민건강보험공단 청구자료 및 의료기관 자료를 기준으로 각 시나리오별로 향후 5년 동안 예상 진료환자 수, 치료 횟수를 추정하였으며, 재정부담을 추계하였다. 결과: 연령관련황반변성에서 현행의 사용형태로 기존 급여기준(평생 14회)이 유지되는 경우(시나리오 1) 2018년 기준 향후 5년간 보험소요재정은 약 4,403억 원으로 추정되었다. 2017년 12월에 변경된 급여기준하에서 5년간 보험소요재정은 약 5,601억 원으로 추정되었다. 2020년 이후 바이오시밀러 급여(시나리오 3), 현재 허가초과 비급여약제인 베바시주맙(시나리오 4)을 급여전환하는 경우에 각각 5,210억 원, 4,197억 원으로 예상되었다. 결론: 본 평생 14회라는 급여기준 삭제로 인해 건강보험 재정이 크게 증가할 것이 예상되었으나 실제 0.1 이하 그리고 반흔화/위축성병변일 경우 급여 중단 등의 새로운 기준으로 중간폭으로 증가하는 것으로 나타났다. 또한 고령화로 인한 연령관련황반변성 유병환자의 증가를 고려할 때 바이오시밀러 및 베바시주맙 도입 등의 정책적 대안도 고려할 수 있다. Purpose: To evaluate the effects of anti‐vascular endothelial growth factor (VEGF) treatment on the healthcare‐related finances of patients with age‐related macular degeneration. Methods: Changes in health care financing due to newly introduced benefit standards were predicted over the coming 5‐year period (2018–2022). We also analyzed the financial impact of scenarios in which agents similar to anti‐VEGF, such as the over‐licensed drug bevacizumab, were introduced. For this purpose, the future number of patients receiving anti‐VEGF treatments was estimated for various scenarios based on National Health Insurance Corporation claims data followed by an estimate of the financial burden. Results: In the case of age‐related macular degeneration, the current standard of care (14 times in a lifetime) was maintained in scenario 1. In 2018, the insurance budget for the coming 5‐year period was estimated at approximately 440.3 billion won. The insurance cost for that period was estimated at approximately 560.1 billion won under the revised standard of December 2017 (scenario 2). For scenarios wherein, after 2020, similar treatments (scenario 3) and bevacizumab (scenario 4) were introduced, the estimated health insurance costs were 521 billion won and 419.7 billion won, respectively. Conclusions: Health insurance costs are projected to increase substantially due to the elimination of the 14 time pay standard; however, the actual budget will only moderately increase, due to new limitations of visual acuity ≤ 0.1 or in case of scarring/ atrophic lesions. Clinically similar agents and bevacizumab could be considered as alternatives to anti‐VEGF treatment for age-related macular degeneration. KCI Citation Count: 0